Shale gas revisited : the European scenario for chemical applications - Craddock, Henry (Knovel, 2014)
The United States is experiencing an energy boom associated with the production of natural gas from dense shale rock formations. This natural gas is an efficient and cheap source of clean-burning fossil fuel and is making a significant contribution to both the energy needs and the economy of the United States. Indeed, some forecasters are predicting that the boom, at least in terms of natural gas provision, could last until 2040. Natural gas extracted from shale rock is also present in many other regions of the world, including Europe. There are, however, some significant differences, particularly with regard to the economics of extraction, the regulatory framework that is in place, and the technical challenges to be faced. All these factors will have a significant impact on the chemistry and the chemicals required for use in fracturing (fracking) fluid, and it is this aspect of shale gas extraction that the current article addresses
Knovel brief article.
Keywords: Shale gas.; Hydraulic fracturing.; Gas fields -- Production methods.; elektronické knihy; electronic books